Conveyor Control System Design using The AT86C51 Microcontroller for Sorting of Sweet Orange (Citrus sinesis L.) based on Their Physical Appearances - Argo, Bambang Dwi; Yogantoro, Nova (Jurnal Teknologi Pertanian, 2007)
Considering the plantation area and annual production, orange is the third mostimportant commodity after banana and mango. Orange from harvesting has varietymaturity and dimension so that needs sorting. Manual sorting cannot yield election ofquality maximally.  The use of automated mechanical sorting for agricultural produces is expected notonly to eliminate boring and time consuming jobs, but also to reduce cost by minimizing oflabors. This particular research was conducted to develop and to test a conveyor controllersystem using a PC equipped with the AT89C51 microcontroller, as an automatedmechanical sorting system for mandarin oranges. The fruit was put on the runningconveyor at which the image was recorded and then input to the developed system. Thefruits classification was based on their physical appearances.  The developed system consisted of two main parts: the mechanical subsystem, i.e. aconveyor which was equipped with the classification mechanism and the electronicssubsystems, i.e. the AT 89C51 microcontroller that serially connected with a PC,functioned as the main controlling unit.  Test results showed that the position control system worked according to theprevious expectation. The average conveyor slip was 6.87 % resulted from the V-belttransmission. The precision of the halted fruit under the imaging unit was greatlyinfluenced by the positioning of the light sensors, rotation of motor, and the position of theimaging camera. The average capacity of the system based on the imaging analysis timeand the motor rotation were 213 fruits/hour (43.07%) and 442 fruits/hour (89.41%),respectively. They were lower than the ideal capacity of  495 fruits/hour.Key words: Mandarin Oranges, Sorting, AT89C51 Microcontroller